PENGARUH MODEL PEMBELAJARAN TEACHING GAMES FOR UNDERSTANDING (TGFU) TERHADAP MINAT SISWA DALAM BEROLAHRAGA DI SMK MUHAMMADIYAH 3 TERPADU PEKANBARU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students’ interest in participating in physical education classes, as indicated by limited participation, feelings of boredom, and the use of monotonous teaching methods. This study aims to determine the effect of the Teaching Games for Understanding (TGfU) model on students’ interest in sports at SMK Muhammadiyah 3 Terpadu Pekanbaru. This research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The sample consisted of 48 students divided into an experimental group and a control group. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The results showed a significant increase in students’ interest in the experimental group after the implementation of the TGfU model, with the mean score rising from 53.91 to 82.60. Meanwhile, the control group, which used conventional methods, only showed a slight increase from 47.28 to 53.68. Hypothesis testing indicated that the TGfU model had a significant effect compared to conventional teaching methods. Therefore, the TGfU model is considered effective in enhancing students’ interest as it provides a more active, enjoyable, and game-based learning experience.